DINAMIKA RESILIENSI PADA ORANGTUA DARI ANAK YANG MENINGGAL KARENA KANKER - Apriyanty, Prita; Garey, Evans (Noetic Psychology, 2017)
Abstract. This research is aimed to explain factors that build resilience towards two cancer volunteers who have lost their children and to describe the process that the cancer volunteers went through to be resilient. Resilience factors are derived from a theory that was developed by Reivich and Shatte (2002). It consisted of emotion regulation, impulse control, optimism, causal analysis, empathy, self-efficacy, and reaching out. The process to be resilient was measured by analyzing the subjectsÃ¢â¬â¢ life events. The result showed that participants were resilient. The process described a systematical journey about the subjectsÃ¢â¬â¢ life events, especially childhood achievements and losing or inconvenience experiences that were contributing to the resilience that the participants already had till now.Keywords: cancer, loss, volunteer resilience